Determining Normal Range of Vitamin D Based on PTH and Bone Mineral Density Changes - B Larijani; Zh Maghbooli; AA Keshtkar; A Soltani; P Ebrahimpour; S Mortaz hejri (Tehran University of Medical Sciences, 2004)
PTH is the most important factor which control calcium homeostasis in the body in this study we tried to determine the normal range of PTH and Vitamin D with examining the relation between PTH and bone density and Vitamin D on the base of bones biological changes. Our subjects were, 20 to 69 years-old men and women of Tehran. Serum volume of PTH and vitamin D in different decades of life had significant difference. Range of serum PTH in osteporotic persons was 29.7-38 pgr/lit (95% SD). This range for non osteporotic persons was 24.33-30.2 pgr/lit. In this study ranges below 18 nmol/lit was considered as severe vitamin D deficiency and 23-36nmol/lit as mild deficiency. So the volume more than 36 nmol/lit volumes was normal range of vitamin D. it seems that biological changes of bones associate more with ranges of vitamin D which causes significant changes in PTH.